Targeted drug nanocrystals for pulmonary delivery: A potential strategy for lung cancer therapy - Kumar M.; Jha A.; DR M.; Mishra B. (My University, 2025)
Introduction: Lung cancer and metastases are major concerns worldwide. Although systemic chemotherapy is the recommended treatment, it is associated with various disadvantages, including non-selective drug distribution and systemic toxicity. In contrast, the pulmonary route ensures the localized delivery of drugs to the lung. Still, the pulmonary route is prone to clearance, limited drug dissolution, and local toxicity to healthy lung cells. Drug nanocrystals provide a potential strategy to enhance the therapeutic efficacy and mitigate the limitations of pulmonary delivery. Areas covered: The development and potential application of nanocrystals in pulmonary delivery, their role in overcoming associated barriers, and strategies for site-specific and stimuli-responsive pulmonary delivery are outlined. This review also traces different in-vitro pulmonary models for assessments of the performance of drug nanocrystals and nanocrystals loaded carriers in pulmonary delivery. Expert opinion: Enhanced stability, high aerosolization performance, better particle size distribution, improved penetration, sustained release of the drug, and minimal excipients usage makes drug nanocrystal an ideal candidate for pulmonary delivery. Besides, drug nanocrystals may provide selective cellular internalization with minimum clearance and maximum deposition. Furthermore, surface modified nanocrystals and nanocrystals in nanocarriers can exhibit a more prolonged, and site-specific release of the drug to cancer cells in the lungs. © 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group.